PREDIKSI LOKASI IUU FISHING DENGAN CLUSTERING DAN TIME SERIES FORECASTING DI PERBATASAN INDONESIA–FILIPINA - Niken Ayu Firdayanti; Trismadi; Gentio Harsono; Yunita Fatma Faidha (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
Illegal, unreported, and unregulated (IUU) fishing still occurs a lot in Indonesia, especially in border areas. Indonesian waters have fishery resources, one of which is in the waters of the Indonesia-Philippines border area, located in the Sulawesi Sea and parts of the Pacific Ocean. Forecasting IUU fishing with past VIIRS satellite data to determine the level of illegal fishing in the next year K-Means Clustering and Time Series are the methods used. Forecasting ARIMA models with Python programming instruments The RMSE prediction results vary in each cluster with a relatively small error value. Predictions for the next 12 months show IUU fishing will occur every month with varying amounts in each cluster. IUU fishing will occur a lot in the K6 cluster in every season. Predictions can be used as a basis for planning scheduled surveillance patrols by taking into account the location and potential timing of IUU fishing.